Learning styles of the Intermediate Intensive I students, during the second semester 2010 at the Foreign Language Departament in the University of El Salvador - Miranda Muñoz, Fermín; Reyes Rivera, Pablo César; Tobar, Claudia Karina (2024)
The findings of this research, focused on the students of the Foreign Language Department, will help teachers to know about the most predominant perceptual learning styles among students and to be reminded that it is important for the students to be provided with a variety of learning experiences in order to facilitate their learning process. By knowing about students’ learning styles, professors will keep in mind that there is a diversity of learning styles among their students which will therefore make professors aware of the variety of teaching strategies they could use in order to address students learning styles properly.